Electrodeposition of iron-molybdenum coatings from citrate electrolyte - Ved, M. V.; Sakhnenko, N. D.; Karakurkchi, A. V.; Zyubanova, S. I. (Pleiades Publishing, 2014)
Specifi c features of the electrodeposition of iron–molybdenum coatings from a citrate electrolyte based on iron(III) sulfate and sodium molybdate in dc and unipolar pulsed modes were studied. It was demonstrated that bright compact coatings with varied content of molybdenum can be produced by varying the relative concentrations of salts of the alloy-forming components and the solution pH. The current density ranges providing the high efficiency of the galvanostastic electrolysis were determined and it was shown that using the pulsed mode makes smaller the amount of nonmetallic impurities in a coating, diminishes its roughness and leads to formation of surface layers with a more uniform composition, The iron–molybdenum coatings exhibit a high corrosion resistance in corrosive media and physicomechanical properties improved as compared with the base metal, which makes it possible to recommend these coatings for protection from corrosive-mechanical disintegration and restoration of the surface of worn articles.